Do apneas and hypopneas best reflect risk for poor outcomes after stroke? - Brown, Devin L. (Sleep Med, 2019)
OBJECTIVE/BACKGROUND: Sleep apnea is associated with poor outcomes after stroke. The best sleep apnea-related measure to capture this relationship is unknown. This measure or its underlying pathophysiology could serve as a treatment target. PATIENTS/METHODS: Within the population-based Brain Attack Surveillance in Corpus Christi project, the ApneaLink Plus was used to perform sleep apnea tests shortly after ischemic stroke (2010–2015). Functional and cognitive outcomes were measured via in-person interviews 90-days post-stroke. Recurrent stroke was assessed longitudinally through active and passive surveillance procedures. After standardization to allow direct comparisons, adjusted models were built for each ApneaLink Plus measure and each outcome, to assess the effect of 1 standard deviation difference in the measure. RESULTS: Among 995 subjects, median age was 67 years (interquartile range: 59, 78) and 52% were women. The respiratory event index had the strongest relationship with functional outcome (mean difference = 0.094, 95% confidence interval (CI): 0.040, 0.147). Desaturations ≤ 85% were associated with worse functional outcome (mean difference = 0.016, 95% CI: 0.002, 0.030), but desaturations ≤ 90% were not. Obstructive apnea index showed the strongest association with cognitive outcome (mean difference = −0.079, 95% CI: −0.162, 0.005), but was not significant. Oxygen desaturation index showed the strongest association with recurrent ischemic stroke (hazard ratio = 1.338, 95% CI:1.016, 1.759). CONCLUSIONS: Measurements easily obtained from a commonly used home sleep apnea test predicted outcomes differentially. This suggests the possibility of different SA-associated targets – perhaps using strategies more tolerable than standard treatment – based on the outcome of interest.